Preventive Effect of Pretreatment with Pitavastatin on Contrast-Induced Nephropathy in Patients with Renal Dysfunction Undergoing Coronary Procedure: PRINCIPLE-II Randomized Clinical Trial - Woong Chol Kang (Journal of Clinical Medicine, 2020)
This study aimed to evaluate the efficacy of pitavastatin pretreatment on contrast-induced nephropathy (CIN) in patients with chronic kidney disease (CKD) after a coronary procedure. This was a prospective, randomized, double-blinded, placebo-controlled, multicenter clinical trial. All consecutive 70 patients with CKD (eGFR < 60 mL/min/1.73 m2) were enrolled and randomized into two groups. Group I consisted of patients who were treated with statins (pitavastatin 4 mg/day) for seven days before and three days after the procedure (n = 37, 52.9%), and group II consisted of patients who were treated with a placebo (n = 33, 47.1%). The primary endpoint was the incidence of CIN, and the secondary endpoints were the change in serum creatinine (∆sCr) level and estimated glomerular filtration rate (∆eGFR) after the procedure. The mean age of the patients (males, 74%) was 70.4 ± 9.0 years. After the coronary procedure, the incidence of CIN was lower in group I than in group II, but the difference was not significant (5.4% vs. 9.1%, p = 0.661). The maximal ∆sCr was lower and the maximal ∆eGFR was higher in group I than in group II, but the difference was not significant (−0.11 ± 0.53 mg/dL and −0.04 ± 0.33 mg/dL, p = 0.678; 4.3 ± 11.2 mL/min/1.73 m2 and −2.9 ± 20.4 mL/min/1.73 m2, p = 0.161, respectively). This study showed the possibility of a clinical benefit of pretreatment with a high dose of pitavastatin for the prevention of CIN in patients with CKD after coronary procedure (ClinicalTrials.gov Identifier: NCT01871792).